Preparation method of modified S-1 zeolite molecular sieve and application of modified S-1 zeolite molecular sieve in photothermal catalysis of carbon dioxide hydrogenation reaction

By modifying S-1 zeolite molecular sieve, it is wrapped with high metal contents Cu and Cr, and is used to photothermal catalyzed carbon dioxide hydrogenation reaction, which solves the problem of low catalytic activity in the prior art and achieves the effect of efficient preparation of C2+ products.

CN119504331APending Publication Date: 2025-02-25NANJING TECH UNIV
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411722317.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art has low apparent quantum efficiency in photothermal catalytic carbon dioxide hydrogenation reaction, resulting in low catalytic activity and is still far from practical application.

Method used

Using modified S-1 zeolite molecular sieve, the copper source, chromium source and silicon source are treated with acid hydrolysis, and the S-1 zeolite molecular sieve wrapped with high metal content Cu and Cr is prepared by template synthesis method, which is used for photothermal catalyzing of carbon dioxide. Hydrogenation reaction.

Benefits of technology

The catalytic efficiency of photothermal catalytic carbon dioxide hydrogenation reaction can be improved, and the high added value C2+ products (such as C2H4 and C2H6) can be effectively prepared, and the catalytic effect is significantly better than the prior art.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504331A_ABST
    Figure CN119504331A_ABST
Patent Text Reader

Abstract

The invention discloses a modified S-1 zeolite molecular sieve and a preparation method thereof, and relates to the field of zeolite molecular sieve catalysts. The modified S-1 zeolite molecular sieve is an S-1 zeolite molecular sieve wrapping high-metal-content Cu and Cr. Through a template synthesis method, a mixture of a copper source, a chromium source and a silicon source subjected to acid hydrolysis treatment and a template agent are subjected to hydrothermal crystallization treatment, and the S-1 zeolite molecular sieve catalyst wrapping high-metal-content Cu and Cr is prepared. The invention also provides application of the catalyst in photo-thermal catalysis of carbon dioxide hydrogenation reaction, C2 + products (such as C2H4 and C2H6) with high additional value can be obtained through the reaction, and compared with the prior art, the catalyst has higher yield, solves the problem of C-C coupling in photo-thermal catalysis of carbon dioxide hydrogenation, and has good industrial application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of zeolite molecular sieve catalysts, and in particular to the application of a modified S-1 zeolite molecular sieve in a photothermal catalytic carbon dioxide hydrogenation reaction. The modified S-1 zeolite molecular sieve is an S-1 zeolite molecular sieve encapsulating a high metal content of Cu and Cr. Background Art

[0002] The uniform pore structure and unique acidity of zeolite molecular sieve make it widely used in industry, but with the continuous improvement of catalyst requirements, a single acidic site can no longer meet the needs of most reactions, so it is the most effective method to modify the zeolite catalyst by compounding with metals or metal oxides. Zeolite can not only stabilize and disperse metals or metal oxides as a carrier, but also use the acidity and pores of zeolite to achieve synergistic catalysis of multiple active sites and improve the selectivity of products. The invention patent of publication number CN115608404B provides a method for preparing a metal-loaded catalyst, which adopts the technical solution of S-1 molecular sieve loading Cu, and the technical solution uses inorganic salts to treat the S-1 molecular sieve carrier, and then metal loading is carried out, which can make the metal in the catalyst evenly dispersed and avoid agglomeration. The technical solution can only improve the surface defects of the catalyst, and does not produce a significant improvement in catalytic performance.

[0003] Carbon dioxide (CO2) produced by burning fossil fuels in power generation and transportation is the main cause of global warming. In order to slow down or minimize the environmental impact of global warming, various methods are being explored to curb CO2 emissions, including more efficient use of fossil fuels and CO2 capture and storage, as well as chemical conversion of CO2 into high-value chemicals and fuels. 2 Hydrogenation to produce high value-added hydrocarbons has attracted widespread attention due to its use of clean and renewable solar energy as an energy source, but the challenge it faces is low apparent quantum efficiency, which leads to low final activity and is still a long way from practical application. Compared with photocatalysis, photothermal systems can effectively utilize full-spectrum sunlight. Especially low-energy infrared light, it mainly achieves thermal energy conversion by utilizing three methods: local surface plasmon resonance of light energy, non-radiative relaxation in semiconductors, and thermal vibration of molecules. Compared with traditional thermal catalytic systems without external heat sources, it is more low-carbon and environmentally friendly. Photothermal catalysis relies on the ability of certain nanometals (with specific catalytic properties) to strongly absorb incident photons and undergo local heating of hundreds of degrees Celsius. This heating allows the catalyst to move within the temperature range where the carbon dioxide hydrogenation process occurs at a reasonable rate.

[0004] Generally, the following reactions are involved in the photothermal catalytic carbon dioxide hydrogenation process:

[0005] CO 2 +H2 →CO+H 2 O (1);

[0006] CO 2 +2H 2 →CH 4 (2);

[0007] nCO+(2n+1)H 2 →C n H (2n+2) +nH 2 O (3);

[0008] nCO+(2n)H 2 →C n H 2n +nH 2 O (4);

[0009] In the process of photothermal catalytic carbon dioxide hydrogenation, the CO and CH produced in reactions (1) and (2) as described above are 4 As C1 products, people are interested in CO, CH 4 The reactions of C1 products have been extensively studied and some progress has been made. In addition, reactions (3) and (4) will also occur. 2 H 4 , C 2 H 6 C with high added value 2+ The reaction energy barrier to be overcome when CH or CO bonds are formed in reactions (1) and (2) is relatively low, and the existing technology for preparing C1 products can achieve good results. The difficulty lies in C 2+ The formation of the product requires a CC coupling reaction between reaction intermediates. The formation of CC bonds in reactions (3) and (4) requires overcoming a larger reaction energy barrier. Summary of the invention

[0010] In view of the defects of the prior art, the present invention provides a modified S-1 zeolite molecular sieve, wherein the modified S-1 zeolite molecular sieve is an S-1 zeolite molecular sieve encapsulating Cu and Cr. The technical solution adopted by the present invention is as follows:

[0011] A modified S-1 zeolite molecular sieve, wherein the molar ratio of Cu, Cr and Si in the modified S-1 zeolite molecular sieve is 10:10:(75-500); or the molar ratio of Cu, Cr and Si is 10:(2-14):100;

[0012] The modified S-1 zeolite molecular sieve is prepared by a template synthesis method after acid hydrolysis treatment of a copper source, a chromium source and a silicon source; the acid hydrolysis treatment is to mix the copper source and the chromium source with water, add hydrochloric acid or nitric acid to adjust the pH to 0.9-1.1, and then add a silicon source to react for 20-30 hours;

[0013] The copper source is taken from one of copper nitrate, copper chloride or copper sulfate; the chromium source is taken from one of chromium nitrate, chromium chloride or chromium sulfate; the acid solution is taken from hydrochloric acid or nitric acid; the silicon source is taken from one of tetraethyl orthosilicate, carbon black, silica sol or silicic acid.

[0014] Preferably, the molar ratio of Cu, Cr and Si is 10:10:(70-75).

[0015] Preferably, the molar ratio of Cu, Cr and Si is 10:10:(80N85).

[0016] Preferably, the molar ratio of Cu, Cr and Si is 10:10:100.

[0017] Preferably, the molar ratio of Cu, Cr and Si is 10:10:125.

[0018] Preferably, the molar ratio of Cu, Cr and Si is 10:10:(165-170).

[0019] Preferably, the molar ratio of Cu, Cr and Si is 10:10:250.

[0020] Preferably, the molar ratio of Cu, Cr and Si is 10:10:500.

[0021] Preferably, the molar ratio of Cu, Cr and Si is 10:2:100.

[0022] Preferably, the molar ratio of Cu, Cr and Si is 10:4:100.

[0023] Preferably, the molar ratio of Cu, Cr and Si is 10:6:100.

[0024] Preferably, the molar ratio of Cu, Cr and Si is 10:8:100.

[0025] Preferably, the molar ratio of Cu, Cr and Si is 10:12:100.

[0026] Preferably, the molar ratio of Cu, Cr and Si is 10:14:100.

[0027] Preferably, the copper source is selected from copper nitrate; the chromium source is selected from chromium nitrate; and the silicon source is selected from tetraethyl orthosilicate.

[0028] Preferably, the copper source is selected from copper chloride; the chromium source is selected from chromium chloride; and the silicon source is selected from silica sol.

[0029] Preferably, the copper source is selected from copper sulfate; the chromium source is selected from chromium sulfate; and the silicon source is selected from silicic acid.

[0030] Further preferably, the copper source is selected from copper nitrate; the chromium source is selected from chromium nitrate; the silicon source is selected from tetraethyl orthosilicate; and the molar ratio of the copper nitrate, chromium nitrate and tetraethyl orthosilicate is 10:10:100.

[0031] The present invention also provides the use of the modified S-1 zeolite molecular sieve in the photothermal catalytic carbon dioxide hydrogenation reaction, and the modified S-1 zeolite molecular sieve is used for photothermal catalytic carbon dioxide hydrogenation to prepare C 2 H 6 , C 2 H 4 The preparation method is as follows: CO 2 , H 2 After mixing with modified S-1 zeolite molecular sieve, the light intensity is 20-25Wcm -2 The reaction was carried out for 0.5 to 2 hours under the conditions of

[0032] The reaction gas CO 2 With H 2 According to the volume ratio of CO 2 :H 2 =1:(3-4) addition;

[0033] The modified S-1 zeolite molecular sieve was prepared according to the conditions of 20 mL CO 2 Add 6 mg of modified S-1 zeolite molecular sieve into the feed.

[0034] Preferably, the modified S-1 zeolite molecular sieve is prepared as a catalyst membrane for photothermal catalytic hydrogenation of carbon dioxide to produce C 2 H 6 , C 2 H 4 reaction;

[0035] The preparation steps of the catalyst membrane are as follows: dispersing the modified S-1 zeolite molecular sieve in water at a ratio of 1 to 1.2 g per 1 mL of water, and loading the modified S-1 zeolite molecular sieve on a glass fiber membrane after being evenly dispersed.

[0036] The present invention also provides a method for preparing a modified S-1 zeolite molecular sieve, the preparation steps being:

[0037] S1, taking a copper source, a chromium source and water, mixing them, adding an acid solution to adjust the pH to 0.8-1.2, adding a silicon source for hydrolysis reaction for 24-36 hours; the amount of the copper source, the chromium source and the silicon source added, in molar ratio, is calculated according to the ratio of Cu contained in the copper source: Cr contained in the chromium source: SiO contained in the silicon source. 2 =10:10:(75-500) or 10:(2-14):100; the amount of water added, calculated by mass ratio, is water:silicon source=(0.8-1.2):1;

[0038] S2, heating the product obtained in S1 to remove the solvent, and then calcining it after drying; taking the calcined product and the template agent, mixing them in a mass ratio of 1: (1.4-1.6), and then performing a hydrothermal crystallization treatment;

[0039] S3, taking the hydrothermal crystallization product of S2 and separating the solid, and obtaining the modified S-1 zeolite molecular sieve after calcination and reduction treatment;

[0040] The copper source is taken from one of copper nitrate, copper chloride or copper sulfate; the chromium source is taken from one of chromium nitrate, chromium chloride or chromium sulfate; the acid solution is taken from hydrochloric acid or nitric acid; the silicon source is taken from one of tetraethyl orthosilicate, white carbon black, silica sol or silicic acid.

[0041] A method for preparing a modified S-1 zeolite molecular sieve, characterized in that the preparation steps are:

[0042] S1, taking a copper source, a chromium source and water, mixing them, adding an acid solution to adjust the pH to 0.8-1.2, adding a silicon source for hydrolysis reaction for 24-36 hours; the amount of the copper source, the chromium source and the silicon source added, in molar ratio, is calculated according to the ratio of Cu contained in the copper source: Cr contained in the chromium source: SiO contained in the silicon source. 2 =10:10:(75-500) or 10:(2-14):100; adding; the amount of water added, calculated by mass ratio, is water:silicon source=(0.8-1.2):1;

[0043] S2, heating the product obtained in S1 to remove the solvent, and then calcining it after drying; mixing the calcined product with a template agent in a mass ratio of 1:(1.4-1.6), and then performing a hydrothermal crystallization treatment;

[0044] S3, taking the hydrothermal crystallization product of S2 and separating the solid, and obtaining the modified S-1 zeolite molecular sieve after calcination and reduction treatment;

[0045] The copper source is taken from one of copper nitrate, copper chloride or copper sulfate; the chromium source is taken from one of chromium nitrate, chromium chloride or chromium sulfate; the acid solution is taken from hydrochloric acid or nitric acid; the silicon source is taken from one of tetraethyl orthosilicate, carbon black, silica sol or silicic acid.

[0046] Preferably, the preparation steps are:

[0047] S1, taking copper nitrate, chromium nitrate and water, mixing them, adding hydrochloric acid to adjust the pH to 1, adding tetraethyl orthosilicate to hydrolyze for 24 hours; the amount of copper nitrate, chromium nitrate and tetraethyl orthosilicate added, calculated by molar ratio, is 1:1:10; the amount of water added, calculated by mass ratio, is water:tetraethyl orthosilicate=1:1;

[0048] S2, heating the product obtained in S1 to remove the solvent, heating it at 450° C. for 4 hours after drying, mixing it with tetrapropylammonium hydroxide at a mass ratio of 1:1.5, and performing a hydrothermal crystallization treatment; the hydrothermal crystallization treatment is to heat it at 180° C. for 72 hours in a sealed container;

[0049] S3, take the hydrothermal crystallization product of S2, separate the solid, heat it at 500N600℃ for 4N6h, and then place it in H 2 Reduce at 600-800℃ in air for 2h.

[0050] Beneficial Effects

[0051] The present invention discloses a modified S-1 zeolite molecular sieve, which is a S-1 zeolite molecular sieve with high metal content of Cu and Cr. The modified S-1 zeolite molecular sieve is prepared by acid hydrolysis of a copper source, a chromium source and a silicon source and then by a template synthesis method. The present invention also provides the use of the catalyst in a photothermal catalytic carbon dioxide hydrogenation reaction, and the reaction can obtain high value-added C 2+ Products (such as C 2 H 4 , C 2 H 6 ), and compared with the existing technology, it has higher catalytic efficiency and good prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 XRD diagrams of the catalysts prepared in Example 1 and Comparative Example 1N3;

[0053] Figure 2 is a SEM image of the catalyst prepared in Example 1;

[0054] Figure 3 The nitrogen adsorption and desorption curves of the catalysts prepared in Example 1 and Comparative Examples 1 to 3 are shown;

[0055] Figure 4 The C of the catalysts prepared in Example 1 and Comparative Examples 1 to 3 during the photothermal catalytic carbon dioxide hydrogenation reaction for 15 min 2+ Selectivity performance map;

[0056] Figure 5It is a comparison diagram of the catalyst effects of Example 1 and the catalyst of the prior art;

[0057] Figure 6 This is a test result diagram of the photothermal catalytic carbon dioxide hydrogenation reaction of the product prepared in Example 1;

[0058] Figures 7 to 21 This is a graph showing the test results of photothermal catalytic carbon dioxide hydrogenation reaction of the catalysts prepared in Examples 2 to 14 and Comparative Examples 1 to 3.

[0059] Among them, Figures 6 to 21 For detailed description of the test products and corresponding characteristic peaks, please refer to Test Example 2 and Test Example 3. DETAILED DESCRIPTION

[0060] In order to explain the technical content, structural features, purpose and effect of the technical solution in detail, the following is a detailed description in combination with specific embodiments and accompanying drawings. The English names or codes of chemical reagents appearing in the following text are explained here:

[0061] The copper nitrate described in the embodiment is copper nitrate trihydrate (Cu(NO 3 ) 2 ·3H 2 O, molecular weight 241.6016), chromium nitrate is chromium nitrate nine hydrate (Cr(NO 3 ) 3 9H 2 O, molecular weight 400.148), tetraethyl orthosilicate with a purity of 98.5% (C 2 H 5 O) 4 Si (molecular weight is 208.327); TPAOH is tetrapropylammonium hydroxide.

[0062] Example 1

[0063] 1.7131g of copper nitrate and 2.8373g of chromium nitrate were mixed and added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of tetraethyl orthosilicate was slowly added. After hydrolysis for 24 hours, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to be thoroughly dried to finally obtain an amorphous dry powder, which was then air-baked at 450°C for 4 hours.

[0064] Take 1 g of the calcined sample in a 5 mL sample tube, add 1.5 g of 25% TPAOH as a template, shake evenly, and put it into a stainless steel hydrothermal autoclave with a polytetrafluoroethylene liner for static hydrothermal crystallization at 180° C. for 3 days.

[0065] After crystallization, the solid was separated by filtration, washed with deionized water until neutral, dried at 100 °C overnight, ground into powder, and calcined at 550 °C in air for 5 h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cu 10 Cr 10 @S-1.

[0066] Take 6 mg of the reduced sample, disperse it in 5 mL of deionized water, and pump it onto the glass fiber membrane to make a catalyst membrane with a diameter of 15 mm. After filtration, put the catalyst into a freeze dryer to dry it for later use.

[0067] Photothermal catalysis was carried out in a customized photothermal catalytic reactor. During the reaction, the catalyst membrane prepared above was placed in the bracket of the closed reactor. After vacuuming for 10 minutes, CO was quantitatively injected into the reactor. 2 and H 2 After a period of reaction under the irradiation of a simulated light source xenon lamp, 100 μL of gas was extracted into a chromatographic detection product equipped with TCD and FID detectors.

[0068] The corresponding relationship between the mass ratio of raw materials and the molar ratio of Cu, Cr and Si in the prepared catalyst is illustrated by Example 1 as follows:

[0069] In this embodiment, the copper source is copper nitrate, the chromium source is chromium nitrate, and the silicon source is tetraethyl orthosilicate; the corresponding relationship between the mass ratio of the raw materials and the molar ratio of Cu, Cr, and Si in the prepared catalyst is:

[0070] 1.7131 g copper nitrate (the raw material is selected from Cu(NO 3 ) 2 ·3H 2 O, molecular weight is 241.6016) corresponds to 0.00709 mol of Cu(NO 3 ) 2 ·3H 2 O, which contains 0.0709 mol of Cu atoms;

[0071] 2.8373 g chromium nitrate (the raw material is selected from Cr(NO 3 ) 3 9H 2 O, molecular weight 400.148) corresponds to 0.007.9 mol of Cr(NO 3 ) 3 9H 2 O, which contains 0.0709 mol of Cr atoms;

[0072] 15g tetraethyl orthosilicate (the raw material is selected from (C 2 H 5 O) 4 Si, molecular weight 208.327) corresponds to 0.0709 mol (C 2 H 5 O) 4 Si, which contains 0.0709 mol of Si atoms;

[0073] Therefore, the molar ratio of Cu, Cr and Si in the catalyst prepared in this embodiment is 0.00709:0.00709:0.0709 (10:10:100).

[0074] Example 2

[0075] 1.7131g of copper nitrate and 0.5675g of chromium nitrate were mixed and added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of tetraethyl orthosilicate was slowly added. After hydrolysis for 28h, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to be thoroughly dried to finally obtain an amorphous dry powder, which was then air-baked at 470°C.

[0076] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 570℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 3h is denoted as Cu 10 Cr 2 @S-1.

[0077] Example 3

[0078] 1.7131g of copper nitrate and 1.1349g of chromium nitrate were mixed and added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of tetraethyl orthosilicate was slowly added. After hydrolysis for 24 hours, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to be thoroughly dried to finally obtain an amorphous dry powder, which was then air-baked at 450°C.

[0079] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cu 10 Cr 4 @S-1.

[0080] Example 4

[0081] 1.7131g of copper nitrate and 1.7024g of chromium nitrate were mixed and added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of tetraethyl orthosilicate was slowly added. After hydrolysis for 24 hours, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to be thoroughly dried to finally obtain an amorphous dry powder, which was then air-baked at 450°C.

[0082] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cu 10 Cr 6 @S-1.

[0083] Example 5

[0084] 1.7131g of copper nitrate and 2.2698g of chromium nitrate were mixed and added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of tetraethyl orthosilicate was slowly added. After hydrolysis for 24 hours, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to be thoroughly dried to finally obtain an amorphous dry powder, which was then air-baked at 450°C.

[0085] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cu 10 Cr 8 @S-1.

[0086] Example 6

[0087] 1.7131g of copper nitrate and 3.4047g of chromium nitrate were mixed and added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of tetraethyl orthosilicate was slowly added. After hydrolysis for 24 hours, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to be thoroughly dried to finally obtain an amorphous dry powder, which was then air-baked at 450°C.

[0088] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cu 10 Cr 12 @S-1.

[0089] Example 7

[0090] 1.7131g of copper nitrate and 3.9722g of chromium nitrate were mixed and added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of tetraethyl orthosilicate was slowly added. After hydrolysis for 24 hours, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to be thoroughly dried to finally obtain an amorphous dry powder, which was then air-baked at 450°C.

[0091] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cu 10 Cr 14 @S-1.

[0092] Example 8

[0093] 0.3426g of copper nitrate and 0.5675g of chromium nitrate were mixed and added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of tetraethyl orthosilicate was slowly added. After hydrolysis for 24 hours, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to be thoroughly dried to finally obtain an amorphous dry powder, which was then air-baked at 450°C.

[0094] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cu 2 Cr 2 @S-1.

[0095] Example 9

[0096] 1.1349g of copper nitrate and 0.6852g of chromium nitrate were mixed and added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of tetraethyl orthosilicate was slowly added. After hydrolysis for 24 hours, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to be thoroughly dried to finally obtain an amorphous dry powder, which was then air-baked at 450°C.

[0097] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cu 4 Cr 4 @S-1.

[0098] Example 10

[0099] 1.0278g of copper nitrate and 1.7024g of chromium nitrate were mixed and added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of tetraethyl orthosilicate was slowly added. After hydrolysis for 24 hours, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to be thoroughly dried to finally obtain an amorphous dry powder, which was then air-baked at 450°C.

[0100] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cu 6 Cr 6 @S-1.

[0101] Embodiment 11

[0102] 1.3705g of copper nitrate and 2.2698g of chromium nitrate were mixed and added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of tetraethyl orthosilicate was slowly added. After hydrolysis for 24 hours, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to be thoroughly dried to finally obtain an amorphous dry powder, which was then air-calcined at 450°C.

[0103] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cu 8 Cr 8 @S-1.

[0104] Example 12

[0105] 2.0557g of copper nitrate and 3.4047g of chromium nitrate were mixed and added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of tetraethyl orthosilicate was slowly added. After hydrolysis for 24 hours, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to be thoroughly dried to finally obtain an amorphous dry powder, which was then air-baked at 450°C.

[0106] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cu 12 Cr 12 @S-1.

[0107] Embodiment 13

[0108] 2.3983g of copper nitrate and 3.9722g of chromium nitrate were mixed and added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of tetraethyl orthosilicate was slowly added. After hydrolysis for 24 hours, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to be thoroughly dried to finally obtain an amorphous dry powder, which was then air-baked at 450°C.

[0109] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cu 14 Cr 14 @S-1.

[0110] Embodiment 14

[0111] 0.3426g of copper nitrate and 0.5675g of chromium nitrate were mixed and added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of tetraethyl orthosilicate was slowly added. After hydrolysis for 24 hours, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to be thoroughly dried to finally obtain an amorphous dry powder, which was then air-baked at 450°C.

[0112] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cu 2 Cr 2 @S-1.

[0113] Embodiment 15:

[0114] 0.9533g of copper chloride and 0.8714g of chromium chloride were mixed and added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of silica sol was slowly added. After hydrolysis for 24 hours, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to be thoroughly dried to finally obtain an amorphous dry powder, which was then air-baked at 450°C.

[0115] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cu 2 Cr 2 @S-1-I.

[0116] Embodiment 16:

[0117] 1.1345g copper sulfate and 2.7808g chromium sulfate were mixed and added to 15g deionized water. Then 0.3g hydrochloric acid was added dropwise to adjust the pH to about 1. 15g silicic acid (H 2 SiO 3 After 24 hours of hydrolysis, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven for thorough drying to finally obtain an amorphous dry powder, which was then air-calcined at 450°C.

[0118] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cu 2 Cr 2 @S-1-II.

[0119] Comparative Example 1

[0120] Take 15g of deionized water, then add 0.3g of hydrochloric acid dropwise to adjust the pH to about 1, and slowly add 15g of tetraethyl orthosilicate. After hydrolysis for 24h, stir the mixed solution at 90℃ to remove the solvent to obtain a solid silicon source, and place it in a 100℃ oven to dry thoroughly to finally obtain an amorphous dry powder, which is then air-calcined at 450℃.

[0121] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample was reduced at 700 °C in air for 2 h and was labeled S-1.

[0122] Take 6 mg of the reduced sample, disperse it in 5 mL of deionized water, and pump it onto the glass fiber membrane to make a catalyst membrane with a diameter of 15 mm. After filtration, put the catalyst into a freeze dryer to dry it for later use.

[0123] Comparative Example 2

[0124] 1.7131g of copper nitrate was added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of tetraethyl orthosilicate was slowly added. After hydrolysis for 24 hours, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to dry thoroughly to finally obtain an amorphous dry powder, which was then air-calcined at 450°C.

[0125] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cu 10 @S-1.

[0126] Take 6 mg of the reduced sample, disperse it in 5 mL of deionized water, and pump it onto the glass fiber membrane to make a catalyst membrane with a diameter of 15 mm. After filtration, put the catalyst into a freeze dryer to dry it for later use.

[0127] Photothermal catalysis was carried out in a customized photothermal catalytic reactor. During the reaction, the catalyst membrane prepared above was placed in the bracket of the closed reactor. After vacuuming for 10 minutes, CO was quantitatively injected into the reactor. 2 and H 2After a period of reaction under the irradiation of a simulated light source xenon lamp, 100 μL of gas was extracted into a chromatographic detection product equipped with TCD and FID detectors.

[0128] Comparative Example 3

[0129] 2.8373g of chromium nitrate was added to 15g of deionized water, and then 0.3g of hydrochloric acid was added dropwise to adjust the pH to about 1, and 15g of tetraethyl orthosilicate was slowly added. After hydrolysis for 24 hours, the mixed solution was stirred at 90°C to remove the solvent to obtain a metal-containing solid silicon source, and then placed in a 100°C oven to dry thoroughly to finally obtain an amorphous dry powder, which was then air-baked at 450°C.

[0130] Take 1g of the above calcined sample in a 5mL sample tube, add 1.5g of 25% TPAOH as a template, shake evenly, put it into a stainless steel hydrothermal kettle with a polytetrafluoroethylene liner and hydrothermally crystallize it at 180℃ for 3 days. After the crystallization is completed, the solid is separated by filtration, washed with deionized water until neutral, dried at 100℃ overnight, ground into powder, and calcined at 550℃ in air for 5h to remove the template, and then heated in 10% H 2 / 90%N 2 The final sample obtained by reduction at 700℃ in air for 2h is denoted as Cr 10 @S-1.

[0131] Take 6 mg of the reduced sample, disperse it in 5 mL of deionized water, and pump it onto the glass fiber membrane to make a catalyst membrane with a diameter of 15 mm. After filtration, put the catalyst into a freeze dryer to dry it for later use.

[0132] Test Example 1

[0133] The samples prepared in Example 1 and the comparative example were subjected to structural characterization and relevant performance tests. The results are as follows: Figure 1-3 As shown:

[0134] Figure 1 3 and 4 are XRD diagrams of the sample of Example 1 and the comparative sample. The peaks exhibited by these samples are typical structural diffraction peaks of MFI zeolite, indicating that the crystallinity of the samples is good and the encapsulation of metal Cu and Cr does not reduce the crystallinity of the samples.

[0135] Figure 2 This is the SEM picture of the sample in Example 1. It can be seen that after doping with 10% Cu and 10% Cr, the morphology is still relatively regular and hexagonal.

[0136] Figure 3The nitrogen adsorption-desorption curves of the sample of Example 1 and the sample of the comparative example are shown in the figure. The sample shows a typical mixed adsorption curve of type I. The specific surface area of ​​the comparative example 1 is larger, and the specific surface areas of the example 1 and the comparative examples 2 and 3 are close, because the metal doping causes some pores to be blocked, resulting in a decrease in the specific surface area.

[0137] Test Example 2

[0138] The catalyst prepared in Example 1 was subjected to a photothermal catalytic carbon dioxide hydrogenation reaction, and the reaction equation is as follows:

[0139] CO 2 +H 2 →CO+H 2 O

[0140] nCO+(2n+1)H 2 →C n H (2n+2) +nH 2 O

[0141] nCO+(2n)H 2 →C n H 2n +nH 2 O

[0142] The photothermal catalytic carbon dioxide hydrogenation reaction was carried out in a batch reactor at normal pressure and room temperature (25°C). During the reaction, 6 mg of the reduced sample was dispersed in 5 mL of deionized water and pumped onto a glass fiber membrane to form a catalyst membrane with a diameter of 15 mm. The sample was transferred to a photothermal catalytic reactor (reactor volume 90 cm 3 ) and fixed on the internal quartz tripod. Before the reaction, evacuate the chamber, flush it with the reaction gas 3-5 times, and add 20 mL CO 2 and 80 mL H 2 , photothermal catalytic carbon dioxide hydrogenation experiments were carried out under 300W xenon lamp irradiation. When the light was irradiated for 5min and 15min, 100μL of gas was taken with a gas-tight needle and tested in a chromatographic detection product equipped with TCD and FID detectors. The reaction product was CH 4 , CO and C 2+ Gas (such as C 2 H 4 , C 2 H 6 ).

[0143] Taking Example 1 as an example, the product of the photothermal catalytic carbon dioxide hydrogenation reaction was detected and analyzed by a chromatographic detection device.

[0144] The chromatographic detection equipment is equipped with a TCD (thermal conductivity detector) and a FID (hydrogen ion flame detector), and can perform TCD and FID detection on a single sample at the same time; the temperature of the TCD detection environment is 120°C and the pressure is 147KPa; the temperature of the FID detection environment is 260°C and the pressure is 147KPa;

[0145] When the photothermal catalytic carbon dioxide hydrogenation reaction was carried out for 15 minutes, 100 μL of gas was sampled from the reactor for detection.

[0146] Combination Figure 6 The test results are described, wherein the test results of the product obtained in Example 1 include C1 product (CH 4 , CO), also includes C 2+ Product (C 2 H 4 , C 2 H 6 ).in, Figure 6 (Upper) part is CH 4 , CO detection results. The characteristic peak at about 6 to 7 minutes in the figure is CH 4 Gas, the characteristic peak at about 8 to 10 minutes is CO gas; Figure 6 (Lower) is C 2 H 4 , C 2 H 6 The detection results show that the characteristic peak at about 3 to 4 minutes is C 2 H 6 , the characteristic peak at about 4 to 5 minutes is C 2 H 6 gas;

[0147] Step 1: C 2 H 6 Take the yield calculation process as an example

[0148] Output (C 2 H 6 ) = product peak area in the spectrum (C 2 H 6 ) / slope of product standard curve (C 2 H 6 )×injection volume conversion factor×reactor volume / standard molar volume / unit conversion factor

[0149] Yield (C 2 H 6 ) = Output (C 2 H 6 ) / metal composition ratio coefficient / catalyst mass×time conversion coefficient

[0150] Among them, the product peak area (C 2 H 6 )Depend on Figure 6 (lower) The test data obtained in the part, the value is 3.6041; the slope of the product standard curve (C 2 H 6 ) is measured by debugging the instrument before this test, and its value is 0.1849; the metal composition ratio coefficient is the sum of the Cu metal / Si element composition molar ratio (1:10) and the Cr metal / Si element composition molar ratio (1:10) in the catalyst prepared in Example 1, and its value is 0.2; the injection volume conversion coefficient is the conversion coefficient between the test sampling volume (100 μL) and the product standard curve test sampling volume (500 μL), and its value is 5; the reactor volume is 90; the standard molar volume is 22.4; the unit conversion coefficient is the conversion value when the dimension is adjusted comprehensively, and its value is 1000000; the time conversion coefficient is calculated according to 60min / 15min, and its value is 4.

[0151] According to the formula, C 2 H 6 The yield was 31.5 mmol g -1 h -1 .

[0152] Step 2: Calculate CH 4 Yield, CO yield, C 2 H 4 Yield, total yield, conversion rate, C 2 +Selectivity

[0153] Use the same calculation process as step 1 to calculate CH 4 ,CO,C 2 H 4 The difference is that the product peak area and the slope of the product standard curve in the formula are replaced by CH 4 ,CO,C 2 H 4 The corresponding values ​​and other parameter values ​​(metal composition ratio coefficient, injection volume conversion coefficient, reactor volume, standard molar volume, unit conversion coefficient, catalyst mass, time conversion coefficient) remain unchanged in this test example. Specifically:

[0154] The product peak area (CH 4 ), the product peak area (CO) in the spectrum is from Figure 6 (above) obtained;

[0155] The product peak area (C 2 H 4 )from Figure 6 (below) obtain;

[0156] The slope of the product standard curve (CH 4 ) is measured by debugging the instrument before this test, and the value is 0.1849;

[0157] The slope of the product standard curve (CO) was measured by debugging the instrument before this test, and the value was 0.1849;

[0158] The slope of the product standard curve (C 2 H 4 ) is measured by debugging the instrument before this test, and the value is 0.1849;

[0159] According to the formula, CH 4 The yield was 86.0 mmol g -1 h -1 ; CO yield was 111.1 mmol g -1 h -1 ; C 2 H 4 The yield was 14.0 mmol g -1 h -1 ;

[0160] The total yield is C 2 H 6 Yield, C 2 H 4 Yield, CH 4 The sum of the yield and CO yield is 242.6 mmol g -1 h -1 ;

[0161] The conversion rate is calculated as follows: Conversion rate = (CH 4 Output + CO output + C 2 H 4 Output × 2 + C 2 H 6 Output × 2) / CO 2 The molar amount of feed was calculated to be 9.5% conversion rate;

[0162] C 2+ Selectivity is the main target product C 2 H 4 , C 2 H 6 The target product CH 4 The difference between the CO yield and the CO yield is one of the indicators for characterizing the catalytic effect of the catalyst. The calculation formula is: 2+ Selectivity = (C 2 H 4 Output × 2 + C 2 H 6 Output × 2) / (CH 4Output + CO output + C 2 H 4 Output × 2 + C 2 H 6 Output × 2); by calculation, we can get C 2+ The selectivity was 31.6%.

[0163] Test Example 3:

[0164] The photothermal catalytic carbon dioxide hydrogenation reaction and the determination of yield, conversion rate and selectivity were carried out with reference to the conditions of Test Example 2, and only the type of catalyst involved in the reaction was changed. The catalysts prepared in Examples 2 to 14 and Comparative Examples 1 to 3 were selected for photothermal catalytic carbon dioxide hydrogenation reaction.

[0165] The products of the photothermal catalytic carbon dioxide hydrogenation reaction were detected and analyzed by chromatographic detection equipment, and the obtained spectrum was Figures 7 to 21 , obtain the product peak areas in the spectra of Examples 2 to 14 and Comparative Examples 1 to 3;

[0166] Figures 7 to 12 The time and order of the peaks in the test results are Figure 6 About the same;

[0167] Figures 13 to 18 The test results of CH 4 , CO detection results. The characteristic peak at about 6 to 8 minutes in the figure is CH 4 Gas, the characteristic peak at about 12 to 14 minutes is CO gas; the lower part of the figure is C 2 H 4 , C 2 H 6 The detection results show that the characteristic peak at about 3 to 4 minutes is C 2 H 6 , the characteristic peak at about 4 to 5 minutes is C 2 H 6 gas;

[0168] Fig.19 The test results showed that no C-containing products were generated;

[0169] Fig. 20 The test results showed that no C 2+ The characteristic peak of the product at about 2 to 3 minutes is CH 4 Gas, the characteristic peak at about 4 to 6 minutes is CO gas;

[0170] Fig.21 The detection results show that CH 4 Gas, C 2 H 6gas, CO gas, the first characteristic peak at 2 to 4 in the figure is CH 4 Gas, the second characteristic peak is C 2 H 6 Gas, the characteristic peak at about 4 to 6 minutes is CO gas.

[0171] According to step 1 and step 2, the CH 4 Yield, CO yield, C 2 H 4 Yield, C 2 H 6 Total yield, conversion rate, C 2+ Selectivity, the obtained data are summarized in Table 1, and the sample names in the table correspond to the names of the catalysts prepared in Examples 1 to 14 and Comparative Examples 1 to 3.

[0172] Table 1: Summary of catalyst selectivity, conversion rate and yield

[0173]

[0174]

[0175] The catalyst prepared in the embodiment of the present invention and the catalyst provided by the prior art were used in the photothermal catalytic carbon dioxide hydrogenation reaction. 2 By comparing the better results of conversion rate (corresponding to the total yield in Table 1), it can be seen that the catalytic effect of the modified S-1 zeolite molecular sieve provided by the present invention in the photothermal catalytic carbon dioxide hydrogenation reaction is significantly better than that of the prior art, and the sample prepared in Example 1 performs best.

[0176] Prior art catalysts and literature sources are as follows:

[0177] ① Catalyst CoFe-650; catalytic effect: 0.627 mmol g -1 h -1 ;

[0178] Source: Advanced Microstructures, 2017; Title: Alumina-SuppoSed CoFe Alloy Catalysts Derived from Layered-Double-Hydroxide Nanosheets for Efficient Photothermal C0 2 Hydrogenation to Hydrocarbons;

[0179] ② Catalyst Fe 3 0 4; Catalytic effect: 11.2 mmol g -1 h -1 ;

[0180] Source: ACS Catalysis 2020; Title: Photothermal Conversion of CO 2 withTunable Selectivity Using Fe Based Catalysts:From Oxide to Carbide:

[0181] ③Catalyst Fe 3 C; catalytic effect: 10.9 mmol g -1 h -1 ;

[0182] Source: ACS Catalysis 2020; Title: Photothermal Conversion of CO 2 withTunable Selectivity Using Fe Based Catalysts: From Oxide to Carbide;

[0183] ③ Catalyst Co-CoO x / MAO; catalytic effect: 2.1mmol g -1 h -1 ;

[0184] Source: Angewandte Chemie International Edition 2023; Title: Co 0 _Co δ+ Interface Double-Site-Mediated CC Coupling for the Photothermal Conversion of CO 2 in to Light Olefins;

[0185] ④ Catalyst Co / MAO; catalytic effect: 4.9mmol g -1 h -1 ;

[0186] Source: Angewandte Chemie International Edition 2023; Title: Co 0 _Co δ+Interface Double-Site-Mediated CC Coupling for the Photothermal Conversion of CO 2 in to Light Olefins;

[0187] ⑤ Catalyst CoO / MAO; catalytic effect: 23.8mmol g -1 h -1 ;

[0188] Source: Advanced Functional Materials; Title: Co 0 _Co a+ Interface Double-Site-Mediated CC Coupling for the Photothermal Conversion of CO 2 in to LightOlefins.

[0189] It should be noted that, although the above embodiments have been described in this article, the patent protection scope of the present invention is not limited thereby. Therefore, based on the innovative concept of the present invention, changes and modifications made to the embodiments described herein, or equivalent structures or equivalent process changes made using the contents of the present invention specification and drawings, directly or indirectly applying the above technical solutions to other related technical fields, are all included in the patent protection scope of the present invention.

Claims

1. Application of a modified S-1 zeolite molecular sieve in photothermal catalytic carbon dioxide hydrogenation reaction, characterized in that: The molar ratio of Cu, Cr and Si in the modified S-1 zeolite molecular sieve is 10: 10: (75~500); or the molar ratio of Cu, Cr and Si is 10: (2~14):

100.

2. The use according to claim 1, characterized in that: The molar ratio of Cu, Cr and Si is 10: 10: (70-75); Or the molar ratio of Cu, Cr and Si is 10: 10: (80-85); Or the molar ratio of Cu, Cr and Si is 10: 10: 100; Or the molar ratio of Cu, Cr and Si is 10: 10: 125; Or the molar ratio of Cu, Cr and Si is 10: 10: (165-170); Or the molar ratio of Cu, Cr and Si is 10: 10: 250; Or the molar ratio of Cu, Cr and Si is 10: 10: 500; Or the molar ratio of Cu, Cr and Si is 10:2:100; Or the molar ratio of Cu, Cr and Si is 10:4:100; Or the molar ratio of Cu, Cr and Si is 10:6:100; Or the molar ratio of Cu, Cr and Si is 10:8:100; Or the molar ratio of Cu, Cr and Si is 10: 12: 100; Or the molar ratio of Cu, Cr and Si is 10:14:

100.

3. The use according to claim 1, characterized in that: The modified S-1 zeolite molecular sieve is prepared by a template synthesis method after subjecting a copper source, a chromium source and a silicon source to acid hydrolysis treatment; the acid hydrolysis treatment is to mix the copper source and the chromium source with water, add hydrochloric acid or nitric acid to adjust the pH to 0.9-1.1, and then add a silicon source to react for 20-30 hours; The copper source is taken from one of copper nitrate, copper chloride or copper sulfate; the chromium source is taken from one of chromium nitrate, chromium chloride or chromium sulfate; the acid solution is taken from hydrochloric acid or nitric acid; the silicon source is taken from one of tetraethyl orthosilicate, white carbon black, silica sol or silicic acid.

4. The use according to claim 3, characterized in that: The copper source is selected from copper nitrate; the chromium source is selected from chromium nitrate; the silicon source is selected from tetraethyl orthosilicate; Or the copper source is selected from copper chloride; the chromium source is selected from chromium chloride; the silicon source is selected from silica sol; Alternatively, the copper source is selected from copper sulfate; the chromium source is selected from chromium sulfate; and the silicon source is selected from silicic acid.

5. The use according to claim 3, characterized in that: The copper source is selected from copper nitrate; the chromium source is selected from chromium nitrate; the silicon source is selected from tetraethyl orthosilicate; The molar ratio of the copper nitrate, chromium nitrate and tetraethyl orthosilicate is 10:10:

100.

6. The use according to claim 1, characterized in that: The modified S-1 zeolite molecular sieve is used for the photothermal catalytic hydrogenation of carbon dioxide to prepare C2H6 and C2H4.

7. The use according to claim 6, characterized in that: After mixing CO2, H2 and modified S-1 zeolite molecular sieve, the light intensity was 20~25 W cm -2 The reaction was carried out for 0.5-2 h under the conditions of The reaction gases CO2 and H2 are added in a volume ratio of CO2:H2=1:(3-4); The modified S-1 zeolite molecular sieve was added in a ratio of 6 mg of the modified S-1 zeolite molecular sieve per 20 mL of CO2.

8. The use according to claim 6, characterized in that: The modified S-1 zeolite molecular sieve is prepared as a catalyst membrane for the photothermal catalytic hydrogenation of carbon dioxide to produce C2H6 and C2H4; The preparation steps of the catalyst membrane are as follows: the modified S-1 zeolite molecular sieve is dispersed in water at a ratio of 1 to 1.2 g per 1 mL of water, and loaded on a glass fiber membrane after being evenly dispersed.

9. A method for preparing a modified S-1 zeolite molecular sieve, characterized in that: The preparation steps are: S1, take copper source, chromium source and water, mix them, add acid solution to adjust the pH to 0.8-1.2, add silicon source for hydrolysis reaction for 24-36 hours; the addition amount of the copper source, chromium source and silicon source, calculated by molar ratio, is Cu contained in the copper source: Cr contained in the chromium source: SiO2 contained in the silicon source = 10: 10: (75-500) or 10: (2-14): 100; the addition amount of the water, calculated by mass ratio, is water: silicon source = (0.8-1.2): 1; S2, heating the product obtained in S1 to remove the solvent, and then calcining it after drying; mixing the calcined product with a template in a mass ratio of 1: (1.4-1.6), and then performing a hydrothermal crystallization treatment; S3, taking the hydrothermal crystallization product of S2 and separating the solid, and obtaining the modified S-1 zeolite molecular sieve after calcination and reduction treatment; The copper source is taken from one of copper nitrate, copper chloride or copper sulfate; the chromium source is taken from one of chromium nitrate, chromium chloride or chromium sulfate; the acid solution is taken from hydrochloric acid or nitric acid; the silicon source is taken from one of tetraethyl orthosilicate, white carbon black, silica sol or silicic acid.

10. The preparation method according to claim 9, characterized in that: The preparation steps are: S1, take copper nitrate, chromium nitrate and water, mix them, add hydrochloric acid to adjust the pH to 1, add tetraethyl orthosilicate to hydrolyze for 24 hours; the amount of copper nitrate, chromium nitrate and tetraethyl orthosilicate added is calculated by molar ratio, and is added according to 1: 1: 10; the amount of water added is calculated by mass ratio, and is added according to water: tetraethyl orthosilicate = 1: 1; S2, heating the product obtained in S1 to remove the solvent, heating at 450-470 °C for 4 h after drying, mixing with tetrapropylammonium hydroxide at a mass ratio of 1:1.5, and performing hydrothermal crystallization treatment; the hydrothermal crystallization treatment is heating at 180 °C for 72 h in a closed container; S3, take the hydrothermal crystallization product of S2 and separate the solid, heat it at 550-570 °C for 4-6 h, and then reduce it at 700-750 °C in a H2 atmosphere for 2 h.

Citation Information

Patent Citations

  • Process for producing light olefins by using a ZSM - 5 - based catalyst

    CN103402632A

  • Carbon dioxide conversion to fuels and chemicals

    CN105339336A

  • Process for producing light olefins by using a ZSM-5-based catalyst

    CN106588529A

  • Composite catalyst, preparation method thereof and preparation method of ethylene

    CN110314696A

  • Composite catalyst, preparation method thereof and preparation method of ethane

    CN110314698A